(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
This study focused on cattle urine utilization as bio-fertilizer and bio-pesticide and its effectiveness on boro rice production comparing with chemical fertilizer and chemical pesticides. Three groups were divided into completely randomized design (CRD) to conduct the experiment. No chemical/bio pesticides and/or fertilizers is being applied in the control group (T0).The second group (T1) is being applied by chemical fertilizer and pesticides in recommended dose. The third group (T2) is being applied by cattle urine as biofertilizer and bio-pesticides in calculative dose. The germinated rice plant BINA boro rice (variety 28) was transferred to a well-prepared rice field after 21 days. The rice field was prepared using cow urine as bio fertilizer. The bio fertilizer solution prepared from mixing cow dung with cow urine (1:1) and then the solution was diluted into1: 9 with water. One kg of fresh neem leaves were kept in 10 L (liters) container with cow urine and allowed 28 days for fermentation. Meanwhile, one liter of the solution extracted from neem leaves was mixed with 10L of fresh water in a ratio of 1:10 to produce a bio pesticide. Cow urine as bio-fertilizer was applied one thousand liters per hectare in boro rice production which was repeated every 28 days from transplant to harvest. Bio pesticide was applied one thousand two hundred liters per hectare by nozzle spraying at 15-day intervals from planting to flowering in boro rice production. Likewise the chemical pesticide was being applied at seven-day intervals. Plant height, chlorophyll content, number of the tiller/hill and grain yield was observed as growth and yield parameter respectively. The tallest plant height and chlorophyll content were 76 cm and 46.5 from T2 on day 45 and 30 respectively, but number of effective tiller per hill, the maximum final score was 14 fromT1.For all treatments, the mean production became identical. However, T2 delivered the highest grain yield at 5.85 t/ha. In yield parameter chemical fertilizer and chemical pesticide (T1) and bio fertilizer and biopesticide (T2) group was non-significant, but in pest infestationbio fertilizer and biopesticide (T2) group was lower. Vol. 9, No. 2, August 2022: 165-169